Using the multidimensional prognostic index for treatment decisions and monitoring in frail older patients - Arduino A. Mangoni (Geriatric Care, 2017)
The routine applicability of clinical guidelines and disease-specific end-points in frail older patients is problematic because of the exclusion of this group from clinical trials, their limited life expectancy, the co-existence of multiple disease states and poor functional status, and the presence of complex drug-drug and drug-disease interactions. In this context, the use of patient-centred end-points that include measures of quality of life might be particularly useful for designing tailored treatment strategies, monitor progress and, ultimately, improve outcomes. The multidimensional prognostic index, an objective, quantifiable, and validated scoring system based on core domains of the comprehensive geriatric assessment, might represent an important tool for the development of clinical guidelines that take into account measures of frailty and patientcentred end-points. However, research is warranted to investigate whether this approach leads to more effective and safe management strategies in old age.